SMARTPHONE: FRIEND OR FOE? UNCOVERING THE DARK SIDE OF DIGITAL ADDICTION - Moesarofah, Moesarofah (Jurnal Konseling Pendidikan Islam, 2024)
Smartphones have become an integral part of modern society, offering a wide range of functions and various positive and negative consequences. Smartphone addiction is associated with adverse mental health outcomes, underscoring the need for further exploration of mental health problems caused by intense smartphone use. The research aims to analyze the prevalence of smartphone addiction and the factors underlying it; as well as the psychological and physiological mechanisms underlying this relationship. The research design uses an exploratory approach to analyze the phenomenon of smartphone addiction in depth, regarding individual lives. Data collection uses a literature review, while data analysis is carried out thematically, and credibility is tested by checking data sources. The research results show that the prevalence of smartphone addiction ranges between 10% - 60% of smartphone users in most of the population, and the percentage is higher for male participants than female participants. The research contributions and implications provide important insights into the phenomenon of smartphone addiction and creating a healthier relationship with technology, by highlighting the prevalence of smartphone addiction in various populations, as well as explaining the psychological and physiological mechanisms underlying the relationship through the interaction of the dopaminergic system, emotion regulation, and the development of the disorder mental health.